Blunt pancreatic trauma: A Western Trauma Association critical decisions algorithm. Issue 3 (18th March 2023) - Moren, Alexis M.; Biffl, Walter L.; Ball, Chad G.; de Moya, Marc; Brasel, Karen J.; Brown, Carlos V.R.; Hartwell, Jennifer L.; Inaba, Kenji; Ley, Eric J.; Moore, Ernest E.; Peck, Kimberly A.; Rizzo, Anne G.; et al.
Abstract : The algorithm addresses the workup, diagnosis, and treatment of blunt pancreatic injury. A high degree of clinical suspicion for injury is often necessary. Recommendations include non-operative management for low-grade and operative management for high-grade injuries. Abstract : BACKGROUND: The Western Trauma Association (WTA) has undertaken publication of best practice clinical practice guidelines on multiple trauma topics. These guidelines are based on scientific evidence, case reports, and best practices per expert opinion. Some of the topics covered by this consensus group do not have the ability to have randomized controlled studies completed because of complexity, ethical issues, financial considerations, or scarcity of experience and cases. Blunt pancreatic trauma falls under one of these clinically complex and rare scenarios. This algorithm is the result of an extensive literature review and input from the WTA membership and WTA Algorithm Committee members. METHODS: Multiple evidence-based guideline reviews, case reports, and expert opinion were compiled and reviewed. RESULTS: The algorithm is attached with detailed explanation of each step, supported by data if available. CONCLUSION: Blunt pancreatic trauma is rare and presents many treatment challenges. Abstract :